Holistic precision wellness: Paving the way for next‐generation precision medicine (ngPM) with AI, biomedical informatics, and clinical medicine - Sawsan G. A. A. Mohammed; M. Walid Qoronfleh; Ahmet Acar; Nader I. Al‐Dewik (FASEB BioAdvances)
Abstract A “quiet revolution” in medicine has been taking place over the past two decades. There are two converging dynamic forces that have propelled precision medicine to the limelight, garnering wide public attention. The first driver is the realization that populations within a disease area can be stratified, thus developing therapies tailored to their specific needs, and the capability to identify these populations by analyzing large, diverse datasets. The second driver is technology advances in multi‐omics approaches and applications (i.e., molecularly informed medicine) enabling a more comprehensive portrait of disease biology. This promises to not only accelerate the development of precision medicine processes but also presents challenges for healthcare professionals and health systems that are struggling to interconnect and integrate disparate data sources into a cohesive clinical strategy to the benefit of their patients. We coin here the term next‐generation precision medicine (ngPM), which is bound to become conventional in the clinics sooner or later. Artificial intelligence (AI) and machine learning (ML) in healthcare have transformative potential and are a strategic response to today's challenges and tomorrow's opportunities. The chief challenges here are how well precision medicine (PM) permeates primary care to become a standard of care and drive toward precision wellness or precision lifestyle (ngPM), while ensuring access to care is feasible, streamlined, and routine. We present here a perspective that would harness the power of ngPM for precision wellness.